Seizing the opportunity: the emergence of shared leadership during the deployment of an integrated performance management system - Pierre-Luc Fournier; Line Moisan; Denis Lagacé (BMC, 2022)
Abstract Background Performance management systems have been introduced in health and social services institutions to improve organizational performance, supporting the emergence of new management behaviors that are more rooted in collaborative management practices. This study aims to understand how different leadership styles emerge through the implementation of a performance management system and its related tools, and how these can foster distributed leadership. Methods Over two years, the implementation of an integrated performance management system supporting the integration of social services for children, youth, and families was studied at a recently merged Canadian healthcare organization. Qualitative analysis of data collected from 15 interviews, 3 focus groups, and over 350 h of non-participant observation was conducted. Results The results show that leadership evolved to adapt to the context of organizational integration and was no longer confined to a single manager. Transformational leadership was needed to encourage the emergence of a new integrated performance management system and new behaviors among middle managers and team members. Transactional leadership was legitimized through the use of a status sheet when the integration project did not deliver the expected results. Both transformational and transactional leadership paved the way to distributed leadership, which in turn promoted collaborative practices associated with activities in control rooms and dialogue stemming from the status sheets. Distributed leadership among team members made a difference in the outcome of the integration project, which became a driver of collaboration. Conclusions The integrated performance management system and the use of its tools can help renew leadership in health and social service organizations. The results lend credence to the importance of distributed leadership in promoting collaborative practices to improve services for children, youth, and families. The results also highlight how various leadership styles can contribute to the emergence of distributed leadership over time.